272p-6=9p+5

Simple and best practice solution for 272p-6=9p+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 272p-6=9p+5 equation:


Simplifying
272p + -6 = 9p + 5

Reorder the terms:
-6 + 272p = 9p + 5

Reorder the terms:
-6 + 272p = 5 + 9p

Solving
-6 + 272p = 5 + 9p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-9p' to each side of the equation.
-6 + 272p + -9p = 5 + 9p + -9p

Combine like terms: 272p + -9p = 263p
-6 + 263p = 5 + 9p + -9p

Combine like terms: 9p + -9p = 0
-6 + 263p = 5 + 0
-6 + 263p = 5

Add '6' to each side of the equation.
-6 + 6 + 263p = 5 + 6

Combine like terms: -6 + 6 = 0
0 + 263p = 5 + 6
263p = 5 + 6

Combine like terms: 5 + 6 = 11
263p = 11

Divide each side by '263'.
p = 0.04182509506

Simplifying
p = 0.04182509506

See similar equations:

| CMa=3+2q | | 3x+66=15 | | 8x+61=-27 | | 6x+55=-35 | | 2x+22=-12 | | 2x+40=12 | | 7-3y=5+4y+11-16y | | 2(x-x-5+2)=6 | | 6x^2+16x-20=0 | | -0.75-x=0.5 | | 4t+9=-8t+13 | | 4x^2-19x+23=-2x+8 | | 8j=69 | | x^2-x-6=3x-1 | | 8-(-9)=1 | | (2x+5)(x-6)=0 | | x^2+12+33=6 | | 3ax-2bx+7=21+x | | 9x^2-0.3x=0 | | M=450-180 | | 12+3x-14.2=x+5.8-3x | | 5+3x=65-3x | | ax-2=4x+a | | 5-(2x-4)=x | | 5x+5=4x-4 | | 3y+5=7y+4 | | 3y+5=7g+4 | | n^2-n-180=0 | | 2x+49=9x-5 | | 7x-5=10(3) | | 12-3(x+2)=x+8 | | 2a-1b=200 |

Equations solver categories